2020
DOI: 10.1016/j.triboint.2019.105907
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale testing of low adhesion effects with small amounts of water in the wheel/rail interface

Abstract: Low adhesion in the wheel/rail contact can be caused by small amounts of water combining with iron oxides. This happens in light rain or at dew point. In small-scale tests, ultra-low adhesion (≤0.05) has not been maintained. The aim here was to see if the mechanism could be realized at a larger scale. Sustained ultra-low adhesion was achieved when water was applied constantly to the wheel/rail contact at a rate of 25µL/s. In these conditions wear debris and oxide was clearly visible in the contact band. Creep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Experiments on a full-scale test rig showed that in case of little water in the contact and high creepage (to generate wear debris) low adhesion conditions may develop [15]. These results also support the modeling results shown in Figure 15 and Figure 16.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Experiments on a full-scale test rig showed that in case of little water in the contact and high creepage (to generate wear debris) low adhesion conditions may develop [15]. These results also support the modeling results shown in Figure 15 and Figure 16.…”
Section: Resultssupporting
confidence: 82%
“…Tribological testing guided the identification of parameters key to the low adhesion mechanisms such as roughness and amount of water. Furthermore, the general characteristic of the adhesion level as a function of the amount of water predicted by the adhesion model was confirmed under rolling contact conditions by the experiments on a full-scale test rig where it has been used to support the specification of these tests [15]. The modeling results have been further supported by results from Twin Disc experiments [14].…”
Section: Discussionmentioning
confidence: 73%
“…Large volumes of water addition may have either diluted the oxide too much or simply washed it away from the contact so low adhesion did not occur. Recent full scale testing has shown that a lower amount of water can produce much lower traction coefficients [16] and twin disc testing, coupled with the syringe plunger used in this work, allows the simple application of very small amounts of water, as well as other third body materials.…”
Section: Year Leaf Contamination Reported No Leaf Contamination Reportedmentioning
confidence: 99%
“…In railway network, an appropriate friction level can accelerate and decelerate a train. However, low friction can cause serious safety problems [1,2]. Meanwhile, the initiation and propagation of rolling contact fatigue (RCF) cracks on railway wheels are serious problems in the field [3,4].…”
Section: Introductionmentioning
confidence: 99%